High-Pressure Assisted Sintering of Ti-20Si-10B and Ti-10Si-5B Powders - Pereira, Wladimir Leite; Trindade Ramos, Erika Coaglia; Ramos, Alfeu Saraiva [UNESP]; Silva, Alexandra Nakano; Caetano Lima, Filipe Tavares; Filgueira, Marcello; Salgado, L.; Ambrozio, F. (Trans Tech Publications Ltd, 2012)
This work presents the structural characterization of Ti-10Si-5B and Ti-20Si-10B (at-%) alloys produced by high-pressure assisted sintering. Sintering was performed in air at 1100 and 1200 degrees C for 60 s using pressure levels of 5 GPa. Structural evaluation of sintered samples was conducted by means of scanning electron microscopy and energy dispersive spectrometry. Samples were successfully consolidated after sintering, which presented theoretical density values higher than 99%. The microstructures of the sintered Ti-10Si-5B and Ti-20Si-10B alloys revealed the presence of the Ti-SS, TiB, TiB2, Ti5Si3, Ti5Si4, TiSi, and TiSi2. phases. A small amount of Ti6Si2B was formed after high-pressure assisted sintering of the Ti-20Si-10B alloy (5GPa, 1100 degrees C for 60 s) indicating that equilibrium structures were not achieved during short sintering times. No oxygen and carbon contamination was detected in structures of Ti-Si-B alloys after high-pressure sintering at 1100 and 1200 degrees C without controlled atmosphere.
Keywords: titanium alloys; electron microscope; powder metallurgy; sintering